Aberrant regional homogeneity of resting-state executive control, default mode, and salience networks in adult patients with moyamoya disease. - Lei, Yu; Su, Jiabin; Jiang, Hanqiang; Guo, Qihao; Ni, Wei; Yang, Heng; Gu, Yuxiang; Mao, Ying (Brain Imaging & Behavior, 2017)
Aberrant local connectivity within cerebral intrinsic connectivity networks (ICNs) at rest has not been reported in adult moyamoya disease (MMD). Our aim was to examine the regional homogeneity (ReHo) of executive control (ECN), default mode (DMN), and salience networks (SN) in patients with executive dysfunction to explore the underlying mechanism. Twenty-six adult patients with MMD and 24 normal control (NC) subjects were recruited. Executive function was evaluated by Trail Making Test Part B (TMT-B) and executive subtests of Memory and Executive Screening (MES-EX). Compared with NC, the case group exhibited ReHo decrease mainly in the frontal and parietal gyrus, and increase only in the left middle temporal gyrus. Subsequent ICNs analysis indicated that compared with NC, patients with MMD exhibited significantly decreased ReHo in the dorsolateral prefrontal cortex (DLPFC) and inferior parietal gyrus (IPG) of left ECN; the IPG, superior frontal gyrus, and DLPFC of the right ECN; the right precuneus, left medial superior frontal gyrus, and right medial orbitofrontal gyrus of the DMN; as well as the left middle frontal gyrus and right supplemental motor area of SN. When referring to the Suzuki's 6-stage classification, a trend of ReHo decrease with disease severity was observed in all of the ICNs examined, but only bilateral ECNs reached statistical significance. Finally, only bilateral ECNs exhibited a significant correlation of averaged ReHo values with executive performance. Our results provide new insight into the pathophysiology of adult MMD.